SOURCES AND MECHANISMS OF FORMATION OF GASEOUS HYDROCARBONS IN SEDIMENTARY ROCKS - Galimov E.M. (My University, 1988)
Accepted concepts of principal stages of hydrocarbon formation fail to satisfactorily explain the accumulation of supergiant gasfields in West Siberia, U.S.S.R., such as for example Urengoy, which comprise 30% of the proven gas reserves of the world. A new mathematical model has been developed which applies the concept of activation energy distribution to the formation of gases. Characteristic differences in the molecular structure of humic and sapropelic source organic matter are expressed in different activation energy distributions. The model allows the calculation of isotope values for different types of organic matter and their dependence on maturity. Application of the model to West Siberia suggests that the supergiant gas accumulations in Urengoy are more likely formed from terrestrial organic matter through thermochemical reactions at moderate depths and are not the result of either deep, overmature, or bacteriogenic processes. The new mathematical model suggests that humic organic matter, in general, has a high methane-generating capacity at comparably low maturities of organic matter equivalent to 0.5–0.7% on the vitrinite reflectance scale.